An Educational Intervention to Improve Knowledge of Local Medicinal Plants among Students Conducting Final Projects on Herbal Medicine Development - Hartanti, Dwi; Utaminingrum, Wahyu; Zain, Dodi Siraj Mu'amar; Hamad, Alwani (Mattawang: Jurnal Pengabdian Masyarakat, 2025)
The diversity of medicinal plants found in Banyumas Regency has encouraged the Faculty of Pharmacy at Muhammadiyah University of Purwokerto to develop medicines from these natural ingredients actively. This is demonstrated through research projects, such as student final assignments, in this field. However, there are still many students from the Faculty of Pharmacy, UMP, who exhibit a gap between their high enthusiasm and limited in-depth knowledge of local medicinal plants, resulting in a weak scientific and cultural basis for their research in their final assignments. This community service activity aimed to enhance students’ knowledge and understanding of local medicinal plants, thereby supporting the quality and progress of their final assignments, which included topics related to herbal medicines. The method employed was a knowledge-refreshing program through education and hands-on practice. The activity involved 18 students (14 undergraduate and 4 postgraduate) and was conducted in July 2025. The stages included a pretest, education using leaflets and posters, field plant identification, and a Posttest. The program’s effectiveness was analyzed statistically using a T-test to compare the pretest and Posttest scores. The results indicated a highly significant increase in knowledge. The average Posttest scores (99.3 - 100.0) far exceeded the pretest scores (80.0 - 83.3), with a p-value < 0.05. This proves that the applied educational and practical methods were highly effective. A positive impact of this initiative was observed in the accelerated completion of final projects, where 7 students successfully defended their undergraduate theses with grades of A/A- and 4 other students completed their proposal seminars. In conclusion, this community service significantly improved students’ knowledge of local medicinal plants. The combined approach of visual education and field-based identification practice proved effective in equipping students with a solid understanding of their research subjects, which ultimately contributed directly to the timely and quality completion of their final assignments.